Palliative Extubation in Pediatric Patients in the Intensive Care Unit and at Home: A Scoping Review - Joana Neto; Hugo Jorge Casimiro; Paulo Reis-Pina (Hindawi Limited, 2023)
Aim. This scoping review is aimed at systematically mapping the evidence on palliative extubation in the pediatric intensive care unit. Methods. MEDLINE, EBSCO, and Cochrane databases were searched for articles published between January 2018 and December 2022, in English. Critical appraisal of sources of evidence was done using the Joanna Briggs Institute tools. PRISMA guidelines for scoping reviews were followed. Results. Six studies were included, with 366 patients, from the USA (n=4), Brazil (n=1), and Germany (n=1). Three were high-quality studies, two were moderate, and one was a low-quality study. Most studies were retrospective analysis; two were narrative approaches; two were evidence-based recommendation and quality improvement project; one study was a prospective intervention. Conclusion. Symptom control is crucial pre- and postextubation. A checklist (symptom management and family support) and a postdebriefing template improve team communication and staff support postextubation. Critical care transports from the hospital are feasible to provide extubation at home. A framework addressing common planning challenges and resource management is recommended for extubation at home. The provision of pediatric palliative extubation is necessary since futile measures and prolongation of suffering violate the principle of nonmaleficence. Future research on this subject will result in more benefits for patients, parents, and professionals.